Tourism images for three Highland destinations in Malaysia as perceived by tourists. - Aziz, Azlizam; Zainol, Nurul Amirah (Forest Research Institute Malaysia, 2010)
This paper focuses on comparing the destination image among the three highlands in Malaysia (Cameron Highlands, Fraser's Hill and Genting Highlands) as perceived by the tourists. A self-administered survey was used to collect data from 1200 respondents intercepted by using stratified sampling technique. Forty-one image attributes were factor analysed and compared among the three highlands using Multivariate Analysis of Variance (MANOVA). This study managed to identify 6 images for the three destinations and subsequently labelled as "accessibility and services", "local attractions and facilities", "general mood and vacation atmosphere", "leisure and recreational activities", "natural surroundings", and "nature heritage and ambience". Results also indicated several images which are unique to each individual destination. Genting Highlands was perceived to be synonymous with "leisure and recreational activities", Fraser's Hill with "general mood and vacation atmosphere" and Cameron Highlands with "local attractions and facilities". The findings of the study provided theoretical and practical implications for the tourism, authorities of Malaysia in order to manage and promote their destinations in a meaningful way.